OPTIMALISASI MEDIA SOSIAL SEBAGAI MEDIA PEMASARAN DALAM MENINGKATKAN KEMANDIRIAN SECARA FINANSIAL PADA CV. DUA WARNA SUMENEP - Ika Maurifa Sari Putri; Moh Kurdi (Journal MISSY (Management and Business Strategy), 2021)
Social media is an online media that can connect long-distance communication, the process of interaction between one user and another, information can be obtained easily through special application devices using the internet network. Interacting on social networks seems closer and real compared to the presence of one's own neighbors. People are more obsessed with the virtual world. This is what interferes with human attitudes, so that someone prefers to be alone, anti-social tends to be insensitive to the needs of people around him, individualistic and others. The purpose of this study was to find out how optimally the Sumenep Two-Color Advertising & Printing Bureau optimally uses social media in increasing Financial Independence. This study uses descriptive qualitative methods. The location of the research was carried out at the location of the business and the place of product production from the Bureau of Advertising & Printing Two Colors which is located at Jln. Dr. Wahidin No.17c, Pajagalan sub-district, Kota sub-district, Sumenep Regency. The results of this study indicate that the promotion carried out by the Two-Color Advertising & Printing Bureau is still optimizing the old way, namely by promoting through word of mouth. Therefore, it is necessary to optimize social media to advance the company as well as to expand the reach of consumers in order to increase financial independence.